Analysis of Augmented Reality Utilization as Learning Media in Primary Schools - Hidayat, Elsa Septiani; Nurasiah, Iis; Sutisnawati, Astri (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2024)
Learning media plays an important role in increasing the effectiveness of delivering material in elementary schools according to the independent curriculum. The aim of this research is to discuss the use of Augmented Reality technology as a learning medium in elementary schools. Augmented Reality enables interactive visualization of material objects, increasing student interest and understanding. The research method used is qualitative with literature study techniques to analyze the use of Augmented Reality as a learning medium in elementary schools. Data from relevant journals was analyzed using qualitative descriptive methods. The research results show that Augmented Reality, which was originally developed for mobile games, has been adapted into an interesting and fun learning tool for students. Augmented Reality is considered a solution to improve the quality of education by utilizing digital technology. The increase in learning outcomes and students' ability to build knowledge based on learning experiences is proof of the effectiveness of using Augmented Reality media in learning in elementary schools. Thus, the use of Augmented Reality in learning can make a positive contribution to achieving educational goals.